Chemo-physical properties of asbestos bodies in human lung tissues studied at the nano-scale by non-invasive, label free x-ray imaging and spectroscopic techniques. (15th September 2021) - Bardelli, Fabrizio; Brun, Francesco; De Panfilis, Simone; Cloetens, Peter; Capella, Silvana; Belluso, Elena; Bellis, Donata; Di Napoli, Arianna; Cedola, Alessia
Graphical abstract: Highlights: Unaltered lung tissue samples from former asbestos workers were studied. Combined x-ray tomography and x-ray spectroscopy were exploited. The 3D morphology and mass density of selected asbestos bodies were revealed. Quantitative elemental analysis revealed similar composition of the asbestos bodies. The Fe content in the asbestos bodies was higher than that contained in asbestos. Abstract: In the lungs, asbestos develops an Fe-rich coating (Asbestos Body, AB) that becomes the actual interface between the foreign fibers and the host organism. Conventional approaches to study ABs require an invasive sample preparation that can alter them. In this work, a novel combination of x-ray tomography and spectroscopy allowed studying unaltered lung tissue samples with chrysotile and crocidolite asbestos. The thickness and mass density maps of the ABs obtained by x-ray tomography were used to derive a truly quantitative elemental analysis from scanning x-ray fluorescence spectroscopy data. The average mass density of the ABs is compatible with that of highly loaded ferritin, or hemosiderin. The composition of all ABs analyzed was similar, with only minor differences in the relative elemental fractions. Silicon concentration decreased in the core-to-rim direction, indicating a possible partial dissolution of the inner fiber. The Fe content in the ABs was higher than that possibly contained in chrysotile and crocidolite. This finding opens two opposite scenarios, the first with Fe coming from the fiber bulk and concentrating on the surface as long as the fiber dissolves, the second where the Fe that takes part to the formation of the AB originates from the host organism Fe-pool.